Mad Max [videorecording (DVD)] - Gibson, Mel; Samuel, Joanne, 1957-; Keays-Byrne, Hugh, 1947-2020- (Twentieth Century Fox Home Entertainment, 2015)
In a world after a nuclear war, where gas is scarce, civilization is slowly fading away. After one cop's family is killed by a ruthless gang, he goes after them, seeking revenge.